Improving 10th Graders’ English Communicative Competence Through the Implementation of the Task-Based Learning Approach (2016)
This article reports the results of an action-research project focused on improving students’ communicative competence in English through the task-based learning approach. This study was conducted in a co-educational public school in Medellín (Colombia) with thirty-four tenth graders. Actions implemented include the development of a series of tasks and the definition of four thematic units consistent with the syllabus and students’ interests and needs. The results evidence students’ significant improvements in their communicative competence in English. Findings also show that implementation of the task-based approach was affected by factors related to the teachers’ role and others related to students’ performance.